OMENTIN-1 LEVEL IN MIDDLE AGE WOMEN WITH HYPOTHYROIDISM AND THEIR RELATIONS TO RISK FACTORS OF CARDIOVASCULAR DISEASE (Iraqi Journal of Medical Sciences, 2016)
Background: Omentin-1 is fat deposition-specific adipokine that is highly and selectively expressed in visceral adipose tissue. Low circulating levels of Omentin-1 have been associated with endothelial dysfunction and cardiovascular disease. Abnormalities of lipid metabolism associated with subclinical and overt hypothyroidisms patients, low Omentin-1 level can affect risk factors for cardiovascular disease.Objective:To determine the differences in the levels of Omentin-1 in middle age women with subclinical and overt hypothyroidisms and correlate its level with parameters which considered risk factor for cardiovascular disease.Methods: Ninety middle age women divided into three groups as follows: group I consisted of 30 healthy women as a control subject, group II comprised 30 women with subclinical hypothyroidisms, group III include 30 women with overt hypothyroidisms, serum of Omentin-1, high sensitive c-reactive protein and lipid profile levels were evaluated in patients and control groups.Results:Serum omentin-1 levels were significant decreased in patients with subclinical and overt hypothyroidisms compared with control group. Significant negative correlation between omentin-1 and thyroid-stimulating hormone, high sensitive c-reactive protein, total cholesterol, atherogenic index in patients was found. Significant positive correlation was observed between Omentin-1 and high-density lipoprotein in the patients.Conclusion:we conclude that serum Omentin-1 levels were decrease in middle age women with hypothyroidism and its correlate with altering lipid profile, high levels of atherogenic index and high sensitive c-reactive protein, all of these conditions is correlated with cardiovascular disease, so Omentin-1 in hypothyroidism patients is a risk factor for cardiovascular disease, our suggestion that possible follow up serum lipid profile and omentin-1 monthly for middle age women to prevent cardiovascular disease.Keywords: Omentin-1, lipid profile, hypothyroidism disease
Keywords: Omentin1; lipid profile; hypothyroidism disease